RANCANG BANGUN KAMUS MINANG-INGGRIS MENGGUNAKAN BAHASA PEMOGRAMAN HYPERTEXT PROCESSOR (PHP) (Universitas PGRI Sumatera Barat, 2017)
This research is an interdisciplinary research that combine language science and information system that is equipped each other. These two languages are chosen in the study because Minang language is the identity of the authors as a media of communications. So, it will be easier to obtain and understand the data (vocabulary) concrete in a cross of this study. Meanwhile, English language is selected as a reference in translating because it is one of the international languages. That is way every level of society including the small region should be prepare their mindset in facing Asean Economic Community (MEA) in order to able communicate with others. One of the effort that we can do in improving english language by reminding vocabularies. This competence will be solve by using dictionary. Therefore the aims of this study is creating dictionary aplication by using PHP (Hypertext Preprocessor) whether online or offline access. Within the advantageous of PHP, it will be easy for the user to get the close word into the target language. This research used SDLC Method (System Development Life Cycle). This method explain life cycle system development in designing and buliding the information system. Keyword : Hypertext Processor (PHP), dictionary